Job satisfaction and its contributing factors, relationship to economy, analysis among four types of organization - Gardiner, Richard; Zubr, Vaclav; Sokolova, Marcela; Mohelska, Hana (Technological and Economic Development of Economy, 2024)
The study examines job satisfaction among workers in four types of organizations (Czech companies, foreign companies, transitory companies, and state institutions) in the Czech Republic. Using Spector’s determinants of job satisfaction, along with innovation and organizational support, a survey was conducted. The analysis involved multi-linear regression, mean, and standard deviation tests. Results show a positive correlation between job satisfaction and factors like communication, nature of work, co-worker relationships, working conditions, contingent rewards, supervision, promotion, and pay across all organizations. We also observed that innovation had a positive correlation with job satisfaction in foreign companies and state institutions, but the impact was not significant. However, there was a significant inverse relationship between innovation and job satisfaction in Czech and transitional companies, though not significant for transitional ones. Organizational support significantly impacted job satisfaction in Czech and transitional companies, but for foreign companies and state institutions, it was not significant. Consequently, the paper suggests that much attention should be given to the area with less satisfied parameters. This research can guide HR, managers, employers, and policymakers in enhancing worker satisfaction based on their abilities or contributions to organizational effectiveness and improving the organization’s economic situation.